Investigating soil properties on the north and south slopes at different elevations in Al-Jabal Al-Akhdar, Libya - Masoud, Moussa; Abdul-Hamid, Hazandy; Bin Mohamed, Johar; Alsanousi, Attia (Forest science and technology, 2024)
This scholarly study investigated the physicochemical characteristics of soil in the Al-Jabal Al-Akhdar forest, Libya, with a specific focus on the influence of elevation and slope aspects. Fifty-six sample plots were established across varying elevations, each subdivided into four subplots, totaling 224. Soil samples were collected from each subplot at 0-15 cm depth. Results demonstrate significant variations in clay, silt, and sand content with elevation, indicating lower clay and higher sand content at higher elevations. Available water capacity (AWC) increased with altitude on the northern slope, while consistently lower values were observed on the southern slope. Bulk density (BD) decreased with increasing altitude, suggesting less compacted soils at higher elevations. Available phosphorus (Pav), available potassium (Kav), and pH values decreased with increasing altitude on both slopes. Cation exchange capacity (CEC) values varied at altitudes on the northern slope, with higher values observed at mid to high altitudes. Calcium carbonate (CaCO3) decreased with increasing altitude on the northern slope while showing inconsistent trends on the southern slope. Soil organic matter (SOM) content increased with altitude on both slopes. Pearson's correlation and Principal Component Analysis (PCA) examined relationships among soil properties, elevations, and aspects. Elevation positively correlated with AWC and SOM and negatively correlated with clay content, Kav, BD, and pH. PCA identified elevation, aspect, silt content, CaCO3, and electrical conductivity (EC) as primary influencers. SOM exhibited positive correlations with AWC and negative correlations with BD. Soil pH showed a negative correlation with SOM and a positive correlation with CaCO3. Additionally, CaCO3 content was positively correlated with the cation exchange capacity (CEC). These findings contribute to understanding soil property relationships, elevation, and aspect, emphasizing their role in shaping soil ecosystems and nutrient dynamics. Further research is warranted to explore additional factors influencing soil properties and to develop effective nutrient management strategies.